Porto Cidade Saudável: da escala Urbana à escala Humana - Ana Maria de Azevedo Calçada (2022)
To build a new way of interpreting what exists beyond the world of forms is a conscious search for social and ethical existences; each formal position refers to a conception of the world, time and subject2 . The challenge of urbanism in the 21st century is to build interpretative systems of synthesis that know how to reconcile formal responses with criticism, which means, systems that explain art, architecture and the city from the social and political perspectives, but that, at the same time, knows how to make an analysis that rejects simplistic explanations that intend to reduce the complexity of the creative and formal worlds exclusively to economic and ideological conditions. Regarding the emergence of the SARS-CoV-2 virus, which triggered a pandemic and countless deaths all over the world, arose, deep into confinement, an interest in studying the city in light of it's health issues. In the first half of 2020, people witnessed a scenario of inversion of life, in which cities - stages of movement, activity, social interactions (at least apparently) - were deserted. On the other hand, the home unfolded into all possible and impossible functions, serving as an office, atelier, gym, school, office, among other things. Thus, confusing the uses, the spaces, symbology and meaning, and resulting in serious social, physical and psychological problems, which brought to light social and economic differences that start in the habitat and extend to the access to public spaces and services. It is up to the public space to seek to be that stage of equal opportunity of access to the city. Current times are struck by the need to ending a single, neutral and universal ideal, and to give way to new realities, diverse cultures and the struggle for more real rights of equality in difference. The relation between urbanism and epidemiology is nothing new, they developed together throughout the 20th century. In other words, urbanism came to respond to public health problems. The search for the Healthy City - sustainable, human and smart - is, in final analysis, the fair way out of these problems. As much reflection as this new disease may have generated, many of the issues raised are not new, much less those regarding the search for the Healthy City. The crux of the matter is how to face the great social and environmental challenges with a sustainable architecture and participated urbanism, in order to evolve towards equality and the recognition of diversity, towards sustainability understood from the social perspective. This city must seek the health of its inhabitants seeking environmental, political, economic and social health. There is no specific solution to reach the Healthy City, but there are possible answers, it is one of those options that the following dissertation intends to present, using Porto as the starting point of a proposal that encompasses the City, the Neighborhood and the Street.